2021
DOI: 10.1007/s10669-021-09807-1
|View full text |Cite
|
Sign up to set email alerts
|

Entropy maximizing evolutionary design optimization of water distribution networks under multiple operating conditions

Abstract: The informational entropy model for flow networks was formulated over 30 years ago by Tanyimboh and Templeman (University of Liverpool, UK) for a single discrete operating condition that typically comprises the maximum daily demands and was undefined for water distribution networks (WDNs) under multiple operating conditions. Its extension to include multiple discrete operating conditions was investigated experimentally herein considering the relationships between flow entropy and hydraulic capacity reliability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 116 publications
0
2
0
Order By: Relevance
“…The results are reliable and consistent with the on-site construction situation. The entropy-matter-element theory method can be used to evaluate the risks of complex engineering systems [35][36] and further applied to the planning, design, construction, and operation stages of underground engineering.…”
Section: Discussionmentioning
confidence: 99%
“…The results are reliable and consistent with the on-site construction situation. The entropy-matter-element theory method can be used to evaluate the risks of complex engineering systems [35][36] and further applied to the planning, design, construction, and operation stages of underground engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Using statistical modeling, the authors found that joint cost and schedule risk predictions could be made which have utility for programmatic risk analysis. Tanyimboh and Czajkowska (2021) developed and demonstrated a genetic algorithm applied to water distribution networks. The algorithm was designed to maximize flow entropy and minimize construction costs.…”
mentioning
confidence: 99%